Karmic Reckonings: "White Noise", Becker, and the "Bardo Thödol" - Edmunds, Susan (Religion & literature, 2024)
This essay returns to two source texts for Don DeLillo's 1985 novel White Noise to uncover the religious roots of its critique of postwar US society. Ernest Becker's The Denial of Death and the ancient Tibetan Bardo Thödol share a focus on the fear of death. The same fear dominates the consciousness of DeLillo's protagonist, Jack Gladney, a white suburban academic who creates the field of Hitler studies at the height of the Vietnam War. DeLillo closely models the second and third parts of White Noise on the spiritual journey between death and rebirth outlined in the Bardo Thödol, in which a dead person must confront the karmic consequences of past actions in life. I argue that the karmic nature of Jack's encounters with the Airborne Toxic Event and Willie Mink throws his accounts of the narrow scope of Hitler studies into doubt. Instead, drawing on the pairing of Hitler and Vietnam that Becker uses to critique the West's secular religious project of scientific and technological advancement, I read Hitler studies as a signifier for the deadly partnerships that US academia forged with the national security state and the military-industrial complex during and after World War II. The novel's scenes of karmic reckoning subject Jack to postwar histories of mass chemical exposure that constitute the repressed condition of his white suburban comfort and prosperity. But DeLillo also gives Jack a spiritual companion in his stepson Wilder, who models the possibility of a less toxic relationship to the fear of death.